1994
DOI: 10.1128/jvi.68.7.4650-4655.1994
|View full text |Cite
|
Sign up to set email alerts
|

Temporal association of cellular immune responses with the initial control of viremia in primary human immunodeficiency virus type 1 syndrome

Abstract: Virologic and immunologic studies were performed on five patients presenting with primary human immunodeficiency virus type 1 (HIV-1) infection. CD8+ cytotoxic T lymphocyte (CTL) precursors specific for cells expressing antigens of HIV-1 Gag, Pol, and Env were detected at or within 3 weeks of presentation in four of the five patients and were detected in all five patients by 3 to 6 months after presentation. The one patient with an absent initial CTL response had prolonged symptoms, persistent viremia, and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
616
2
13

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,277 publications
(644 citation statements)
references
References 49 publications
13
616
2
13
Order By: Relevance
“…Other studies have shown that most of the CD4 + T cell response can be captured by the combination of these 2 cytokines [21,22]; if IFN-g alone is used as the end point, a portion of the CD4 + T cell response is missed. CD8 + T cells are key effectors for clearing virus-infected cells [23] and have been associated with Downloaded from https://academic.oup.com/jid/article-abstract/194/12/1650/810944 by guest on 30 April 2020 control of lentivirus replication in both nonhuman primates (NHPs) and humans [24][25][26][27][28][29][30][31][32]. Twelve (34%) of the 35 vaccine recipients who received the 4-mg or 8-mg doses had detectable HIV Env-specific CD8 + T cell responses at week 12.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that most of the CD4 + T cell response can be captured by the combination of these 2 cytokines [21,22]; if IFN-g alone is used as the end point, a portion of the CD4 + T cell response is missed. CD8 + T cells are key effectors for clearing virus-infected cells [23] and have been associated with Downloaded from https://academic.oup.com/jid/article-abstract/194/12/1650/810944 by guest on 30 April 2020 control of lentivirus replication in both nonhuman primates (NHPs) and humans [24][25][26][27][28][29][30][31][32]. Twelve (34%) of the 35 vaccine recipients who received the 4-mg or 8-mg doses had detectable HIV Env-specific CD8 + T cell responses at week 12.…”
Section: Discussionmentioning
confidence: 99%
“…Passive transfer of a variety of anti-HIV1-Env antibodies to macaques induces complete or partial protection following vaginal SHIV challenge [34]. Additionally, the decrease of HIV levels in the blood has been associated with high levels of HIV-specific CD8 + T cell activity [35,36] and CD8 + T cell depletion in SIV-infected rhesus macaques causes an increase in plasma viremia [37,38]. Of note, following SIV infection of a natural host there is a general absence of chronic immune activation and this may need to be emulated by candidate vaccine vectors in order to generate appropriate immunity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on acute HIV-1 infections [21,22] showed that early elevation of CD8 + CTL specific for HIV-1 can be observed several weeks after infection, corresponding to the initial decline of HIV-1 plasma viraemia, thus suggesting that CD8 + CTL plays important roles in controlling the virus replication in initial period of HIV-1 infection. Similarly, detections on clinical longterm nonprogressors [23][24][25][26] infected by HIV-1 demonstrated the presence of low viral loads, slower decrease in CD4 + T lymphocyte counts and broad CTL immune responses, supporting the notion that CTL responses may help to curb viral replication in these chronically HIV-1-infected individuals.…”
Section: Discussionmentioning
confidence: 99%